Wetting behaviour and reactivity between liquid Gd and ZrO2 substrate - Turalska P.; Homa M.; Bruzda G.; Sobczak N.; Kaban I.; Mattern N.; Eckert J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The wetting behavior and reactivity between molten pure Gd and polycrystalline 3YSZ substrate (ZrO2 stabilized with 3 wt% of Y2O3)were experimentally determined by a sessile drop method using a classical contact heating coupled with drop pushing procedure. The test was performed under an inert flowing gas atmosphere (Ar) at two temperatures of 1362°C and 1412°C. Immediately after melting (Tm=1341°C), liquid Gd did not wet the substrate forming a contact angle of θ=141°. The non-wetting to wetting transition (θ < 90°) took place after about 110 seconds of interaction and was accompanied by a sudden decrease in the contact angle value to 67°. Further heating of the couple to 1412 °C did not affect wetting (θ=67°±1°). The solidified Gd/3YSZ couple was studied by means of optical microscopy and scanning electron microscopy coupled with X-ray energy dispersive spectroscopy. Structural investigations revealed that the wettability in the Gd/3YSZ system is of a reactive nature associated with the formation of a continuous layer of a wettable reaction product Gd2Zr2O7.